Estimating mode choice: A discrete choice analysis of a park and ride system for Florida road, Durban - Bilala, Nikita (Department of Civil Engineering, 2019)
The majority of roads in Southern Africa have been designed primarily for private vehicle usage, with alternative modes such as public transport and non- motorised transport being largely neglected, and this is also true of Florida Road. Florida Road is located in Morningside, Durban, and has become an iconic landmark street known for its buzzing day and night life. However, due to the lack of adequate parking provision, coupled with increased traffic volumes, this street is plagued by traffic congestion, drivers performing unsafe vehicle manoeuvres as well as illegal parking, contributing to increased driver frustration and the increased possibility of car accidents. In this study, the feasibility of introducing a Park and Ride (P&R) system to Florida Road (from Greyville Racecourse) was investigated. Previous studies have shown that P&R systems can have a positive impact on traffic congestion on the local road network, however, there are not many studies that document the travel impacts and demand for P&R systems of this type – smaller P&R that do not link to major bus or rail public transport systems, but rather operate as “express bus” systems. This dissertation investigated the predicted travel behaviour responses of car users to the introduction of a P&R system to Florida Road from Greyville Racecourse. By doing so, the demand for the service, in terms of choice probabilities, was forecast. Another interest in this study was to examine the influence of current travel behaviour patterns as well as socio demographic characteristics on the predicted demand for the service. A stated preference survey was designed and implemented, which presented respondents with hypothetical choice scenarios involving three modes considered available – car, P&R and Uber with varying levels of service attributes i.e. travel cost, time spent parking, security and headway. A questionnaire asking respondents about their current travel patterns and personal characteristics was also administered. A discrete choice experiment was then carried out. A discrete choice experiment models the stated choices of respondents and provides a relative evaluation on the attributes presented, based on their responses. A multinomial logit model was then used in this experiment, to estimate the results. The results of the discrete choice experiment show that travel cost is one of the most important factors in mode choice evaluation by users of Florida Road. In particular to the P&R system, the service headway as well as presence of car guards/ security at the P&R facility were critical determinants of choice. Employment status was found to have a significant impact on the perceived costs of a trip, particularly trips made by respondent’s private vehicle. Respondents also displayed a preference for P&R for social trips, and work trips, over other modes. The time users spent parking at Florida Road was found to not be a significant deterrent to car usage. Socio – demographic variables such as age and gender were not found to have a significant bearing on mode choice probabilities. To ensure a sustainable demand for the P&R system, P&R service characteristics should be optimised, and the utility of using the P&R service should be higher than that of the other modes considered. From the data analysis, it was evident that for a higher patronage, the cost of using the P&R service should be low, or ideally, the service should be free. Shorter headways between pick – ups/ drop – offs should be maintained. Another important aspect is that, to promote the service, adequate advertising on social media is recommended. Aspects such as parking facility location, bus schedules, costs etc should be highly publicised. A high - quality shuttle bus service should also be provided, to further attract prospective users to the service. For the P&R system to be truly successful, P&R should be also introduced with measures to discourage use of parking bays on Florida, and encourage the use of the P&R service. An option considered is to start charging parking costs for the bays on Florida Road, thereby discouraging the use of this parking. The promotion of public transport, coupled with measures that actively discourage private vehicle usage would add to the attraction of the P&R system.